2010
DOI: 10.1016/j.nano.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated macrophages are predominant carriers of cyclodextrin-based nanoparticles into gliomas

Abstract: The goal of this study was to evaluate the mechanism of cyclodextrin-based nanoparticle (CDP-NP) uptake into a murine glioma model. Using mixed in vitro culture systems, we demonstrated that CDP-NP was preferentially taken up by BV2 and N9 microglia (MG) cells as compared to GL261 glioma cells. Fluorescent microscopy and flow cytometry analysis of intracranial (i.c.) GL261 gliomas confirmed these findings and demonstrated a predominant CDP-NP uptake by macrophages (MP) and MG within and around the tumor site. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 42 publications
1
68
1
Order By: Relevance
“…Besides, the question arises if also tumor-associated macrophages play a role in modulating the nanoparticle uptake in cancer cells leading to a reduced efficacy of nanoparticle-based tumor therapy or whether this is an effect restricted by the vascular endothelium. [58] This study shows that static cell cultures represent a fast and useful tool to assess nanoparticle uptake in general. Assessing nanoparticle uptake in primary endothelial cells is significantly influenced by physiological shear stress.…”
Section: Resultsmentioning
confidence: 83%
“…Besides, the question arises if also tumor-associated macrophages play a role in modulating the nanoparticle uptake in cancer cells leading to a reduced efficacy of nanoparticle-based tumor therapy or whether this is an effect restricted by the vascular endothelium. [58] This study shows that static cell cultures represent a fast and useful tool to assess nanoparticle uptake in general. Assessing nanoparticle uptake in primary endothelial cells is significantly influenced by physiological shear stress.…”
Section: Resultsmentioning
confidence: 83%
“…Macrophages have the ability to migrate in and out of intracranial tumors and distribute to other tumor cells within the CNS [36]. Alizadeh et al [37], recently studied the uptake of cyclodextrin-based NPs into a murine glioma model and showed that these NPs are preferentially taken-up by tumorassociated macrophages. After NP incorporation, these cells distributed within and around the tumor mass indicating that macrophages could vehicle NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Murine GL261 glioma cells were obtained from Dr. Karen Aboody's laboratory in 2006 and stably transfected with firefly luciferase expression vector as described before (14, 15). Positive clones (GL261-luc) were selected using zeocin (1 mg/mL) and G418.…”
Section: Methodsmentioning
confidence: 99%